Sustainability Study of a Residential Building near Subway Based on LCA-Emergy Method - Xinnan Chen; Hairuo Wang; Junxue Zhang; He Zhang; Ashish T. Asutosh; Guodong Wu; Guobin Wei; Yaling Shi; Minghui Yang (Buildings, 2022)
In the context of ecological building and green building popularity, building sustainability assessment is becoming more and more important. In this paper, a comprehensive evaluation platform by coupled LCA method and energy method was designed, verified, and analyzed to assess the sustainability of the building system. The main results illustrated that the construction stage is the most critical stage in terms of emergy angle. From a sustainability perspective, the Emergy Sustainability Indicator was at a moderate level (1.0141), which can be considered to increase the proportion of renewable energy and reduce the proportion of non-renewable resources to improve the sustainability degree. Of the three scenarios designed, the second scenario has the best sustainability in the building system. The unit emergy value of the whole building was also shown to demonstrate the unit emergy of an individual. In order to verify the accuracy of the data, a sensitivity analysis was conducted. Finally, two types of positive measures are proposed to ameliorate the environmental sustainability in the building system, containing the increasing proportion of renewable energy and using recycled building materials.